2010
DOI: 10.1117/1.3463009
|View full text |Cite
|
Sign up to set email alerts
|

Application of an optical clearing agent during noninvasive laser coagulation of the canine vas deferens

Abstract: Abstract. Development of a noninvasive vasectomy technique may eliminate male fear of complications and result in a more popular procedure. This study explores application of an optical clearing agent ͑OCA͒ to scrotal skin to reduce laser power necessary for successful noninvasive laser vasectomy and eliminate scrotal skin burns. A mixture of dimethyl sulfoxide and glycerol was noninvasively delivered into scrotal skin using a pneumatic jet device. Near-infrared laser radiation was delivered in conjunction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
(42 reference statements)
2
20
0
Order By: Relevance
“…A residual water layer present on the skin surface after the cryogen spurt during the procedure may strongly absorb the 980 nm laser radiation, resulting in a much higher temperature rise on the skin surface than for the 808 and 1075 nm wavelengths. It should also be noted that although this study was performed using only canine vas deferens and scrotal skin tissue, ex vivo, we have observed consistent results in previous studies when progressing from ex vivo to in vivo studies [7,8].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A residual water layer present on the skin surface after the cryogen spurt during the procedure may strongly absorb the 980 nm laser radiation, resulting in a much higher temperature rise on the skin surface than for the 808 and 1075 nm wavelengths. It should also be noted that although this study was performed using only canine vas deferens and scrotal skin tissue, ex vivo, we have observed consistent results in previous studies when progressing from ex vivo to in vivo studies [7,8].…”
Section: Discussionsupporting
confidence: 87%
“…During previous studies, we have reported successful targeting, thermal occlusion, and scarring of the vas while preventing scrotal skin injury in ex vivo and in vivo canine models [7,8]. However, the therapeutic window for treatment is relatively narrow.…”
Section: Introductionmentioning
confidence: 94%
“…15 The thermal lesion length is strongly correlated with the 3-mm-diameter laser spot used in these studies and is also similar to measurements reported in previous studies. [7][8][9]14 The thermally coagulated vas was excised for examination to verify the OCT and HFUS images. Figure 5 shows a representative image of the thermally coagulated vas segment, which can be identified by several indicators including blanching and shrinkage of the vas wall.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the experimental setup have been previously reported. 9 A modified, 4-mm-OD, vasectomy ring clamp was used to manually isolate the vas beneath the scrotal skin surface for co-location with the cryogen and laser spots ( Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation